AI-Josyu: Thinking Support System in Class by Real-time Speech Recognition and Keyword Extraction - Matsumoto, Kyohei; Nakanishi, Takafumi; Sakawa, Toshitada; Onodera, Kengo; Orimo, Shinichiro; Kobayashi, Hiroyuki (EMITTER International Journal of Engineering Technology, 2019)
In this paper, we present a thinking support system, AI-Josyu. This system also operates as a class support system which helps to teachers for lightening their work. AI-Josyu is implemented based on media-driven real-time content management framework. The system links real world media and legacy media contents together. In resent years, it is easier to collect a large amount of various kinds of data which are created with sensors in the real world. The system realizes interconnection and utilization of legacy media contents. The legacy media contents are generated and scattered on the Internet. The framework has four modules, which are called â€œacquisition,â€ â€œextraction,â€ â€œselection,â€ and â€œretrieval.â€ The real world media and the legacy media contents are interconnected by these modules. This interconnection includes semantic components. This system records teacher's voice of its lecture in real time and presents retrieved legacy media contents corresponding to subject of the lecture. By this presentation, preparing of the legacy contents is not required. This system automatically retrieves and shows the legacy media contents. This system helps students to understand contents of the lecture. In addition, the system attends to expansion of ideas.Â We constructed the system and conducted the demonstration in class. It shows that the system is helpful to teacher and students for expansion of thinking.